Cinema and poetry in the dark side of the heart,by Eliseo Subiela - Vieira Posada, Gabriel (Folios, revista de la Facultad de Comunicaciones y Filología, 2013)
The relationship between cinema and literature has transformed during the past decades, allowing the emergence of films with great lyricism, freed from the compliance that literature commonly has expected from adapted films. This paper explores poetic cinema through the analysis of a master-piece of Argentine cinema, The dark side of the heart, directed by Eliseo Subiela. It examines how different types of interdiscursive strategies work together in the film, in order to bring closer to the public the poetry pieces on which the film is based. By means of a meticulous selection of poems and songs, Subiela immerses us in a surreal whirlwind of sensations about the search of the dreamed love. Intertexts and paratexts alternate with the satire in a statement that mixes different types of speeches: verbal, visual, mimetic, diegetic and non-diegetic sounds. Consequently, the spectator of The dark side of the heart not only sees but also feels these poems.